To Study the Relationship Between Family Pathology and Depression Proneness Among Adults - Chauhan, Nupur; Singh, Yuvraj; Yashraj (Integrated Journal for Research in Arts and Humanities, 2024)
Background: In today's busy world, familial neglect due to hectic schedules can lead to alienation among family members, affecting behaviour and mental health. Parents' lack of time for children can result in minimal interaction, triggering parental fear, guilt, and a breakdown in trust, often culminating in family pathology and maladaptive behaviour within interactions. Prolonged family pathology can exacerbate depression among members, contributing to rising depression rates and a noticeable absence of familial bonds. Methods: This study utilized a cross-sectional correlational research design and Random sampling to investigate the link between family pathology and depression proneness among married parents aged 35 to 54 in urban Jaipur, India, belonging to middle and high socio-economic status. Sixty participants (30 males, 30 females) were sampled and assessed using the Family Pathology Scale (FPS) by Dr. Vimala Veeraraghavan and Dr. Archana Dogra (2000), alongside the Depression Proneness Scale (DPS) by Dr. Niranjan Prasad Yadav. Statistical analysis included Pearson product-moment correlation to analyse the relationship between family pathology and depression, and a t-test to examine gender differences in depression proneness. Result: Results indicated a moderate positive correlation (R = 0.5246) between family pathology and depression, suggesting that families with higher levels of pathology are more likely to experience depression. However, the t-test value of -0.5993 with 58 degrees of freedom was not significant at the 0.05 level, indicating no gender discrepancy in depression proneness. Conclusion: This study concludes that early assessment of family pathology can reduce the risk of depression by employing interventions such as family therapy, healthy communication, emotional support, stress management, and seeking professional help from mental health professionals. While there is a positive correlation between family pathology and depression proneness, but there is no gender discrepancy in an individual's susceptibility to depression.